A study of the factors that determine product development success in a firm - Teo, Lemmy Kay Chee. (2009)
The development of new products is a high-risk but potentially very rewarding venture. Few businesses can rely on yesterday products to ensure competitive success. In recent years, many companies have attempted to update their product ranges by merging with or acquiring other businesses. However, these routes are often risky and are becoming increasingly expensive. Product development is an effective means for sustaining internal business growth provided it is managed skilfully. This project screens through the work of various prominent product development researchers and by combining various frameworks together, a guideline for new product development is created.